The Depiction of Chinese Cultural Peculiarities - Rakhmonova Saodat Akmal kizi (Genius Journals, 2022)
Understanding the definition of culture is essential for talking about culture differences. About the definition of culture, of course, different people have their own understanding of culture. But American Zhang Jie, associate professor, master, Department of Foreign Language and Literature, China Youth University for Political Sciences, and anthropologist, Alfred Kroeber and Clyde Kluckhohn, explained in his book Culture: “A Critical Review of Concepts and Definitions” (1952), there are more than 160 different kinds of definitions about culture
Keywords: KnowledgeKnowledge; belief; art; habits